Research of the degree of fixation of abrasive particle in the soil - Dvoruk V.І.; Borak, K.V. (Problems of Tribology, 2019)
An adaptation was developed for measuring the soil shear resistance.. Studied the influence of the type and moisture content of the soil, as well as on the content of the root system on it, on the degree of fixation of the abrasive particles in the soil. The regularities of the degree of fixation of the abrasive particles in the soil are established depending on the mentioned factors. The directions of further research are determined